1997
DOI: 10.1016/s1074-7613(00)80386-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth Retardation and Leaky SCID Phenotype of Ku70-Deficient Mice

Abstract: Ku70, Ku80, and DNA-PKcs are subunits of the DNA-dependent protein kinase (DNA-PK), an enzyme implicated in DNA double-stranded break repair and V(D)J recombination. Our Ku70-deficient mice were about 50% the size of control littermates, and their fibroblasts were ionizing radiation sensitive and displayed premature senescence associated with the accumulation of nondividing cells. Ku70-deficient mice lacked mature B cells or serum immunoglobulin but, unexpectedly, reproducibly developed small populations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
367
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(388 citation statements)
references
References 68 publications
18
367
3
Order By: Relevance
“…This agreed well with the results obtained by immunocytochemical analysis (Reeves, 1985;Yaneva et al, 1985;Mimori et al, 1986;Koike et al, 1998). Since both Ku70 and Ku80 monomers are highly unstable compared to their heterodimers (Errami et al, 1996;Gu et al, 1997;Singleton et al, 1997), we were interested in studying the nuclear translocation of Ku80 and its heterodimer partner Ku70. Osipovich et al (1997) reported that mutations in Ku80 corresponding to amino acids 453 and 454 abolished its ability to interact with Ku70, using an in vitro binding assay and the yeast two-hybrid analysis.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This agreed well with the results obtained by immunocytochemical analysis (Reeves, 1985;Yaneva et al, 1985;Mimori et al, 1986;Koike et al, 1998). Since both Ku70 and Ku80 monomers are highly unstable compared to their heterodimers (Errami et al, 1996;Gu et al, 1997;Singleton et al, 1997), we were interested in studying the nuclear translocation of Ku80 and its heterodimer partner Ku70. Osipovich et al (1997) reported that mutations in Ku80 corresponding to amino acids 453 and 454 abolished its ability to interact with Ku70, using an in vitro binding assay and the yeast two-hybrid analysis.…”
Section: Resultssupporting
confidence: 87%
“…Both Ku70 and Ku80 are highly unstable when expressed individually (Satoh et al, 1995). Loss of one of the Ku subunits results in a signi®cant decrease in the steady-state level of the other (Errami et al, 1996;Gu et al, 1997;Singleton et al, 1997). These ®ndings strongly suggest that Ku70 and Ku80 function as heterodimers.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Ku70 À/À and Ku80 À/À mice, while viable, likewise showed increased apoptosis in post-mitotic neural cells, though to a lesser extent than seen in Xrcc4 À/À and Lig4 À/À embryos (Gu et al, 2000). Ku70/80 deficiency also imparts radiation sensitivity, proportional dwarfism, impaired V(D)J recombination, abrogation of DSB repair, predisposition to thymic lymphomas and impaired B-cell development (Nussenzweig et al, 1996;Gu et al, 1997;Ouyang et al, 1997). The DNA-PK phenotype is less severe than that of the Ku-deficient mice, as they exhibit no growth defect or radiation sensitivity despite immunodeficiency (Taccioli et al, 1998;Gao et al, 1998a).…”
Section: Animal Models Of Nhej and Hr Deficienciesmentioning
confidence: 99%
“…NHEJ is critical for differentiating cells to prevent apoptosis of the post-mitotic neurons (Lee and McKinnon, 2007). This is particularly clear in DNA ligase IV and XRCC4-deficient mice (Frank et al, 1998;Gao et al, 1998b), but Ku70 or Ku80 deficiency shows similar defects to a lesser extent (Nussenzweig et al, 1996;Gu et al, 1997). The neuropathy in patients with the LIG4 syndrome and XLF/Cernunnos deficiency is confined to characteristic facial features and microcephaly, suggesting that these mutations do not cause a complete NHEJ deficiency.…”
Section: Intersection Of Nhej With Other Cellular Processesmentioning
confidence: 99%